Educational video game for Flow Education Inc. - Jón Atli Guðlaugsson 1997-; Snorri Vignisson 1997-; Franklin Þór Vale 1997-; Ólafur Barkarson 1998- (2021)
Evolytes is a platform that teaches elementary level math faster and more effectively in a unique, fun and engaging way. Evolytes is a platform that combines book, mobile game, individualized content and an online web monitor. The idea is that playing a game makes math more fun and engaging for children. The game revolves around a character that the students can choose from premade characters with different story arches. Then they will go into the Evolytes universe. Their goal is to capture other Evolytes, battle Evolytes, collect trophies and chests and so forth. To be able to move forward in the game students have to answer math questions correctly. Making the game is our final project for a BSc. in Computer Science at Reykjavík University. This game has been made before and our mission is to make the game in a new programming language with a new Game engine to make it more scalable, easier to run and add in some extra features to improve user experience.